Neutron Induced Reactions on 203Tl at 15.7MeV, 16.0MeV and 18.0MeV - Kagioglou, Maria; Vlastou, Rosa; Diakaki, Maria; Kokkoris, Michail; Chasapoglou, Sotirios; Bari, Zoi; Axiotis, Michail; Lagogiannis, Anastasios (HNPS Advances in Nuclear Physics, 2024)
The aim of the present work is to study the potential channels that result from the interaction of 203Tl with neutrons by bombarding natural TlCl pellet targets with neutron beams at 15.7, 16.0 and 18.0 MeV. The monoenergetic neutron beams were produced at the 5.5 MV Tandem Van de Graff accelerator laboratory of NCSR "Demokritos" by means of the 3H(d,n)4He reaction. The cross section measurements were based on the activation technique and deduced with respect to the 197Au(n,2n)196Au and 27Al(n,α)24Na reference reactions. After the end of the irradiations, the induced activity in the target and reference foils was measured by γ-ray spectroscopy, using High Purity Germanium detectors (HPGe).